2022
DOI: 10.3389/fmars.2022.784481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gonad Reproductive Condition Using Non-invasive Ultrasonography in Red Abalone (Haliotis rufescens)

Abstract: The reproductive status in abalone (Haliotis spp.) can be difficult to discern using traditional visual inspection methods and may therefore rely on lethal histological analyses for a definitive determination. With endangered species of abalone, lethal histological examinations are strictly prohibited due to their imperiled status. This research investigated the effectiveness of using non-invasive ultrasound technology as an alternate means of identifying the reproductive status of abalone rather than through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As part of a broader conservation effort to mitigate the impact of climate change on endangered abalone populations (National Marine Fisheries Service, 2008, we sought to investigate the direct and indirect effects of temperature on dulse and juvenile abalone physiology respectively. Our results contribute to a comprehensive exploration of the effects of ocean warming on abalone physiology, including adult reproductive health, with consequences for hatchery management and juvenile abalone recruitment (Boles et al, 2022(Boles et al, , 2023. Concurrent efforts by Neylan et al (2023), revealed slower growth, delays in fecundity, and decreased gonad tissue thickness on adult abalone when exposed to elevated ocean acidification conditions at 14°C.…”
Section: Indirect Effects Of Temperature On Juvenile Abalone Growthmentioning
confidence: 67%
“…As part of a broader conservation effort to mitigate the impact of climate change on endangered abalone populations (National Marine Fisheries Service, 2008, we sought to investigate the direct and indirect effects of temperature on dulse and juvenile abalone physiology respectively. Our results contribute to a comprehensive exploration of the effects of ocean warming on abalone physiology, including adult reproductive health, with consequences for hatchery management and juvenile abalone recruitment (Boles et al, 2022(Boles et al, , 2023. Concurrent efforts by Neylan et al (2023), revealed slower growth, delays in fecundity, and decreased gonad tissue thickness on adult abalone when exposed to elevated ocean acidification conditions at 14°C.…”
Section: Indirect Effects Of Temperature On Juvenile Abalone Growthmentioning
confidence: 67%
“…We used a Sonosite Edge II Ultrasound System with a HFL50 6‐15 MHz probe (Mechanical Index = 0.7; Thermal Index = 0.1; Read Depth = 6; Exam type = breast) (FUJIFILM Sonosite, Bothell, WA) to examine and measure the gonadal tissue of adult abalone prior to spawning (Boles et al., 2022). We took ultrasound images prior to spawning on the morning of April 2, 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Abalone reproductive anatomy was imaged with a SonoSite Edge II Ultrasound System (FUJIFILM SonoSite Bothell, Washington) using a HFL50 15-6-MHz transducer probe (Mechanical Index=0.7; Thermal Index=0.1; Read Depth=6; exam type: breast). To reduce handling stress, ultrasound examinations were conducted by immersing abalone in seawater affixed to transparency copier film (3M #PP2950, Austin, Texas) shell side down to expose the muscular foot and categorically ranked using established methods (Boles et al, 2022). Abalone gonadal tissue wraps around the outer portion of the cone-shaped digestive gland and is located between the shell and the foot on the right-hand side of the mantle cavity (Figure 1).…”
Section: Ultrasound Assessmentmentioning
confidence: 99%
“…Ultrasound technology has been used by biologists for decades as a non-lethal technique to assess the reproductive health in finfish conservation (Evans et al, 2004;Swanson et al, 2008;Chiotti et al, 2016;Brizendine et al, 2018;Carim et al, 2021) and for commercial aquaculture purposes (Bonar et al, 1989;Blythe et al, 1994;Colombo et al, 2004;Naeve et al, 2018). While ultrasonography had previously been used in paūa (H. iris) to identify shell lesions that diminish the ability of the adductor muscle to properly adhere to the shell, leading to increased mortality (Nollens et al, 2002), only recently has ultrasound technology been successfully used to characterize abalone reproductive state, specifically red abalone gonad condition (Boles et al, 2022). The goal of this study is to assess the use of non-lethal ultrasonography as a technique to monitor the reproductive condition of endangered black and white abalone and to evaluate the applicability of the technology for use in conservation programs.…”
Section: Introductionmentioning
confidence: 99%